Implementation of the Independent Curriculum Policy at Madrasah Tsanawiyah Negeri 1 West Lampung - Liliani, Dewi; Puspawati, Ani Agus; S, Bambang Utoyo; Hermawan, Dedy (Eastasouth Institute, 2025)
One of the innovations in education in facing the development of the era is the implementation of the Independent Curriculum which emphasizes flexible, contextual, and student-centered learning. This study aims to analyze the implementation of the Independent Curriculum at Madrasah Tsanawiyah Negeri 1, West Lampung and the challenges faced in implementing the Independent Curriculum. The data obtained involved observation, interviews, and documentation. The results of the study indicate that the implementation of the Independent Curriculum is running well, supported by the quality of human resources, facilities, and adequate technology. However, there are several obstacles such as the lack of further training and ineffective communication between policy implementers. This study recommends the preparation of more structured regulations and SOPs, increasing routine training, and optimizing the use of technology to support curriculum implementation. These findings are expected to be a reference for madrasas and policy makers in improving the quality of education through the Independent Curriculum.